A new Peruvian species of Enna (Araneae, Lycosoidea, Trechaleidae) - Da Silva, Estevam L. Cruz (Zootaxa, 2013)
The spider genus Enna O. Pickard-Cambridge, 1897 comprises 38 species, distributed from Mexico to Southern Brazil, and is the most diverse genus of Trechaleidae (Platnick, 2013). Enna was revised by Silva et al. (2008) and 13 further species were described by Silva & Lise (2009a, 2009b), Carico & Silva (2010), Silva & Lise (2011) and Silva et al. (2012). Silva & Lise (2010) and Silva et al. (2012) also synonymised two Enna species. Currently, there are 11 Enna species known from Peru (Silva et al. 2008; Silva & Lise 2009a, 2009b, 2011; Carico & Silva 2010; Silva et al. 2012). In this work, a new species of Enna is described and illustrated from Peru. A distribution map is provided.